2015
DOI: 10.1016/j.actbio.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective BSA imprinted polyacrylamide hydrogels facilitated by a metal-coding MIP approach

Abstract: The development of hydrogel-based molecularly imprinted polymer (HydroMIPs) technology for the memory imprinting of proteins and for protein biosensor development presents many possibilities, including uses in bio-sample clean-up or selective extraction, replacement of biological antibodies in immunoassays and biosensors for medicine and the environment. Biosensors for proteins and viruses are currently expensive to develop because they require the use of expensive antibodies. Because of their biomimicry capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…It is interesting to notice that this procedure is reminiscent of the experimental techniques used to produce molecular moulds. [331][332][333][334] …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to notice that this procedure is reminiscent of the experimental techniques used to produce molecular moulds. [331][332][333][334] …”
Section: Discussionmentioning
confidence: 99%
“…Studies on polyacrylamide hydrogel-based MIPs have demonstrated sensitivity and selectivity towards several proteins with different biological roles, sizes and electrochemical activities, namely haemoglobin, myoglobin, cytochrome c, bovine serum albumin (BSA) and catalase [47,48,49]. Further improvements in terms of MIP selectivity have been attempted by including a metal chelating complex comprising bifunctional vinyl groups with the ability to co-polymerize within the polyacrylamide matrix [50]. These advanced imprinted cavities with metal-coding for enhanced selective protein recognition showed higher BSA binding and selectivity.…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…These advanced imprinted cavities with metal-coding for enhanced selective protein recognition showed higher BSA binding and selectivity. These results may be explained by a better macroporosity and stability of the polymer backbone, as well as additional metal contribution to favorable interactions with the protein [50]. Hydrogel polymers undergo a reversible volume transition between swollen and collapsed phases.…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…MIPs found early application for solid phase extraction of drugs and pesticides 27 , and more recently for bioanalyte detection and as biosensors 28, 29 . In particular, hydrogel MIPs based on polyacrylamide (PAA) and derivatives thereof were realised for selective recognition of bio-macromolecules, including, but not limited to, small regularly shaped globular proteins such as bovine serum albumin (BSA) 30, 31 or haemoglobin 32, 33 . Protein-based MIPs were also tested as nucleates for protein crystallisation 34 .
Figure 1Schematic overview of R-MIP preparation.
…”
Section: Introductionmentioning
confidence: 99%